Results of Endoscopic and Open Removal of Hypertensive Subcortical Hematomas - V. G. Dashyan; R. Y. Kryachev; Y. A. Shesterikov; I. M. Godkov; S. V. Tsilina; V. V. Krylov (Неотложная медицинская помощь, 2021)
AIM OF STUDY To compare the effectiveness of surgical treatment of patients with hypertensive intracerebral hematomas (ICHs) of subcortical location and methods of endoscopic aspiration and open removal.MATERIAl AND METHODS The results of surgical treatment of 97 patients with hypertensive subcortical hematomas were analyzed. In group 1 (n=52),endoscopic aspiration of the ICH was performed using a frameless  navigation station, in group 2 (n=45), open removal of the ICH was  performed using a microsurgical method.RESUlTS Mortality among patients in the age group over 71 years after endoscopic aspiration of ICH was significantly lower than after open removal (30.8% and 60%, respectively). With a decrease in the level of wakefulness to sopor, the mortality rate with endoscopic removal was 50%, and with open intervention — 66.7%, with a decrease to coma — 100% in both groups. Among patients of the 1st group with the volume of ICH less than 40 cm3, the lethality was 11.1%, while in the 2nd group this indicator was almost 2 times higher — 20%. With endoscopic removal of an intrauterine device with a volume of 40 to 60 cm3, the mortality rate reached 14.3%, and with an open removal of a hematoma of the same volume, this indicator reached 30%, while the mortality rate in both groups was similar with a volume of an intrauterine device from 61 to 100 cm3 and amounted to 23.1% and 21.4% in the 1st and 2nd groups, respectively. The radicality of hematoma removal in the 1st and 2nd groups was 86.4% and 86%, respectively.CONClUSION Endoscopic removal of hypertensive subcortical hematomas revealed a greater number of patients with good recovery, and postoperative mortality was 11.3% lower than with open removal, which, along with the  simplicity of execution and minimally invasiveness, indicates the safety and  efficiency of endoscopic aspiration for surgical treatment of patients with intracerebral hematomas of subcortical location.